ROLES OF AUTO-CORRECTION TOOLS ON HUMSS STUDENTS’ WRITING SKILLS - T. Sanchez, Avigail; R. Arcila, Kairille France; L. Baldomero, Jerime; P. Cahanding, Kianna Mhae; A. De Leon5, Rachelle Anne; A. Samson, Catherine (International Interdisciplinary Conference on Sustainable Development Goals, 2023)
Auto-correction tools, a product of technological advancement, are now prevalent globally, present and impacting diverse fields. In education, writing is an essential macro skill that an individual must possess or learn and has been transformed by modern learning modalities. Thus, this research paper highlighted the roles of auto-correction tools on the students' writing abilities affecting the variation of their actual English compositions in terms of frequency of errors in vocabulary, in syntax, and in mechanics of writing. Employing a concurrent triangulation mixed method research design, quantitative and qualitative data were analyzed individually and then combined during interpretation. Results reveal that 44% of respondents scored within the "Marginal" range, while the lowest percentages, 28%, fell into the "Satisfactory" and "Poor" categories. With a cumulative mean score of 17.22, the results reflect an average proficiency level in terms of vocabulary, syntax, and writing mechanics. These numerical data also indicates that students over-rely on auto-correction tools, denoting deficiencies in essential writing skills and inaccuracy in their handwritten compositions implying that the students lack mastery in vocabulary, syntax, and mechanics of writing that is expected in their level. However, these tools also offer valuable corrective feedback for vocabulary, grammar, and punctuation. Hence, it is recommended that to enhance writing proficiency while harnessing these tools, targeted instruction and exercises are recommended to ensure students develop mastery in vocabulary, syntax, and mechanics.